2019
DOI: 10.3390/nu11122947
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Rehabilitation in Patients with Malnutrition Due to Crohn’s Disease

Abstract: Background: Crohn’s disease (CD) is a chronic inflammatory bowel disease frequently associated with malabsorption and secondary protein-energy malnutrition (PEM). Methods: Biochemical and clinical data of 63 (34 females, 29 males) patients with PEM due to CD sent to our outpatient unit for nutritional evaluation were retrospectively analyzed. Patients were divided into two groups, according to disease activity. Thirty-eight patients (group A) had the active disease, and 25 patients (group B) suffered from mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…After nutritional therapy, serum BChE significantly improved in CD patients. On the other hand, the increased BChE levels after nutritional support demonstrated the recovery of nutritional status and liver protein synthesis [21]. Thus, we inferred that serum BChE levels may be more closely related to CD than to UC.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…After nutritional therapy, serum BChE significantly improved in CD patients. On the other hand, the increased BChE levels after nutritional support demonstrated the recovery of nutritional status and liver protein synthesis [21]. Thus, we inferred that serum BChE levels may be more closely related to CD than to UC.…”
Section: Discussionmentioning
confidence: 77%
“…In our study, we used body mass index to represent the nutritional status of IBD patients, and we found that body mass index in CD patients was lower than that in UC patients. CD is frequently associated with malabsorption and secondary protein-energy malnutrition [21]. Nutritional interventions for the treatment of CD were consistently effective but were limited and were generally not effective for UC patients [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The primary cause of persistent intestinal inflammation has been linked to undernutrition and dysbiosis of the gut microbiome with PD as some of the major consequences (30)(31)(32)147). The WHO guidelines on the management of diarrhea in HIV-infected infants and children stipulates the use of vitamin A supplementation as a prevention strategy, whereas zinc supplementation, low-osmolarity oral rehydration solution (ORS), and daily micronutrients have been recommended as treatment (148).…”
Section: Discussionmentioning
confidence: 99%
“…Undernutrition is also characterized by functional and structural alterations in the intestinal mucosa, which is associated with chronic intestinal inflammation (22). The impact of undernutrition (30,31) and dysbiosis in the gut microbiome (32) has been hypothesized as a primary cause for persistent intestinal inflammation and epithelial damage.…”
Section: Malnutrition and The Immune System In Hiv-infected Infantsmentioning
confidence: 99%
“…Thus far, several studies have shown a close relationship between malnutrition and decreased quality of life in different populations [7][8][9][10][11][12][13][14], including subjects with IBD [15][16][17]. Malnutrition is frequently observed among patients with CD [18,19], and it is known to be associated with low muscle mass and an impaired functional status [15,17,20,21]. Recently, we have observed reduced muscle strength in CD patients compared to healthy controls, independent of disease activity and gender [21].…”
Section: Introductionmentioning
confidence: 99%